PENGARUH KINERJA KEUANGAN, STRUKTUR MODAL DAN UKURAN PERUSAHAAN TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN SUB SEKTOR MAKANAN DAN MINUMAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2020-2022 - Halimah, Nur; Elly, Moh. Iskak; Vidiyastutik, Elok Dwi (Growth, 2024)
This research aims to determine the influence of financial performance, capital structure and company size on company value. This research uses a quantitative approach based on a cause-and-effect hypothesis. There are 26 food and beverage sub-sector companies listed on the Indonesia Stock Exchange for the period 2020 and 2022. Using sampling criteria, 20 companies were selected as samples, resulting in 60 companies with data value for three years. The research results show that the financial performance variable partially has a positive and significant effect on company value as shown by (t count 5.820 > t table 2.003). On the other hand, the capital structure variable (t count 1.216 < t table 2.003) and the company size variable (t count -1.130 < t table 2.003) do not have a significant effect on company value. Meanwhile, simultaneously financial performance, capital structure and company size have a positive and significant effect on company value (F count 11.511 > F table 2.77). With a standard Beta coefficient of 0.658, the financial performance variable has a dominant influence on company value.